Synthesis and Characterization of Some Inorganic Compounds and Study their Effect in activity of Laccase Produced by Fungal isolate Pleurotus ostreatus - Alias, M .F.; Hashim, A.J .; Kareem, T . A . (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
, The new ligand(OBTMRZ),Bis[4-phenyl-3(2-propenyl)thio-1,2,4- triazole  -5yl] methane  was prepared and characterized by vibrational , spectra  and J>hysical methods,selected metals,which  were Cu11 Zn 11 Mn11,Co11,Fe"  and  Hg11   were  reacted   with  ligand   to  produce   new complexes.Solid  compounds  were   isolated   and   identified   through metal analysis.vibrational  and  electronic   spectra,molar conductivity magnetic susceptibility measurements and other techniques dependingon the  data  obtained,chemical formula  geometry  of  complexes were suggested.Other ligands(OXH,TRZH,OTRZ,BTMRZH2)were prepared and select metals(Cu",znnandMn11)reacted with them to produce complexes.These  complexes  were  characterized  by  infrared   spectroscopy and physical methods .Laccase   was  produce   from  fungal   isolate  P  .ostreatus   using submerge  culture  at 30C0    pH =6.5  after  96 hour  of incubation .The analysis of fungal  filtrate using (HPLC) technique shown  the presence one peak which indicated  , that was partial  purifioo , the flam atomic ab orption technique indicated that the enzyme was contains (2Zn,